2009
DOI: 10.1007/s10900-008-9144-2
|View full text |Cite
|
Sign up to set email alerts
|

Health Status in Immigrants and Native Early Adolescents in Italy

Abstract: The aim of the study was to compare health status between native and immigrant early adolescents in Italy and to analyze related psychosocial factors. Data were taken from "Health Behavior in School Aged Children", a cross-sectional survey investigating health behaviors among early adolescents in selected European countries. A representative sample of 6,744 (50.4% males) Italian students (11, 13 and 15-years-old) completed a questionnaire. Students were assessed for demographics characteristics, socio-economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 34 publications
3
60
1
9
Order By: Relevance
“…Previous surveys on health and well-being indicate that children of foreign extraction (Engström et al 2004;Reinhardt and Madsen 2002;Weathers et al 2008;Vieno et al 2009;Vinnerljung et al 2007;Vuille and Schenkel 2001) and children in single-adult households (RavensSieberer et al 2008;Reinhardt and Madsen 2002;Weitoft et al 2003;Vinnerljung et al 2007) are at higher risk of health problems than other children. A Nordic study with children aged 2-17 based on parental responses showed that children with a foreign background reported significantly higher levels of subjective health complaints (SHC), such as headache, back pain, stomach pain, loss of appetite, dizziness, sleeping disorders, and a lower feeling of wellbeing compared to children in the majority population (Reinhardt and Madsen 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous surveys on health and well-being indicate that children of foreign extraction (Engström et al 2004;Reinhardt and Madsen 2002;Weathers et al 2008;Vieno et al 2009;Vinnerljung et al 2007;Vuille and Schenkel 2001) and children in single-adult households (RavensSieberer et al 2008;Reinhardt and Madsen 2002;Weitoft et al 2003;Vinnerljung et al 2007) are at higher risk of health problems than other children. A Nordic study with children aged 2-17 based on parental responses showed that children with a foreign background reported significantly higher levels of subjective health complaints (SHC), such as headache, back pain, stomach pain, loss of appetite, dizziness, sleeping disorders, and a lower feeling of wellbeing compared to children in the majority population (Reinhardt and Madsen 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent females had more than twice the risk of self-harm than adolescent males, and adolescents of both genders were at the highest risk if their ethnicity was Western European, Eastern European, or mixed (Jablonska et al 2009). Irrespective of parental background, adolescent girls generally report more SHC than boys (Currie et al , 2008Danielsson 2006;Gillander Gådin and Hammarström 2005;Hagquist 2009;Hetland et al 2002;Reinhardt and Madsen 2002;Torsheim et al 2006;Sweeting 2003, 2004;Vieno et al 2009;Vuille and Schenkel 2001;Ö stberg et al 2006). The reasons for this gender pattern have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Outros estudos com adolescentes encontraram nos imigrantes menores níveis de bem-estar subjetivo comparativamente aos nativos (Neto, 2001;Vieno, Santinello, Lenzi, Baldassari, & Mirandola, 2009;Ullman & tatar, 2001).…”
Section: A Prática Desportiva E O Bem-estar Subjetivo Dos Imigrantesunclassified
“…childhood or adolescence (Veling & Susser, 2011;Bomba, Riva, Capelli, Neri, & Nacinovich, 2017), separation or loss of parents or relatives (Morgan et al, 2007;Bourque, van der Ven, Fusar-Poli, & Malla, 2012), perceived discrimination (Berg et. al, 2011), poor social support (Hefner & Heisenberg, 2009;Tonsing, Zimet, & Tse, 2012) and bullying (Vieno, Santinello, Lenzi, Baldassari,& Mirandola, 2009). …”
Section: Introductionmentioning
confidence: 99%